On the definition of negative imaginary system for not necessarily rational symmetric transfer functions - Ferrante, A.; Ntogramatzidis, Lorenzo (IEEE, 2013)
In this paper we provide a definition and characterisation of negative imaginary systems for not necessarily rational but symmetric transfer functions along the same lines of the classic definition of positive real systems. We then derive a necessary and sufficient condition that characterises symmetric negative imaginary transfer functions in terms of a matrix sign condition on the imaginary axis.